Biotechnology for the preparation of functional bread in compliance with the principles of the circular economy - Kryzhova, Maria; Korniienko, Iryna; Yastremska, Larysa (Problems of Environmental Biotechnology, 2024)
The approach to the biotechnology of functional bread preparation in compliance with the principles of circular economy is considered